Measuring methods for the investigation of in‐plane and cross‐plane thermal conductivity of thin films. Issue 1 (17th December 2012) - Völklein, F.; Reith, H.; Meier, A.
Abstract The characterization of the thermal properties of thin film materials is important both for understanding of their structure and conduction mechanisms and for their technical applications. Thermal conductivity and diffusivity are crucial parameters for the design of integrated devices, thermal microsensors and actuators. Reliable system simulation and design optimization of such devices is based on the accurate determination of thermophysical properties. It is therefore highly desirable to acquire such data. Usually, thermal properties of thin films differ considerably from the bulk values, since the parasitic surface effects are much stronger due to the smaller dimensions and aspect ratios. The measurement of these properties is sophisticated and associated with various problems. We report on steady‐state and transient methods for the characterization of in‐plane and cross‐plane film properties by using microelectrothermal chips.